Digestão anaeróbica de água residuária de fecularia em reatores de leito fixo utilizando meio suporte de anéis de bambu e PVC. - Watthier, Elisangela (2011)
The liquid effluent of the starch factories causes serious damage to the environment if discharged without being previously treated, due to the high organic loads and to the presence of cyanide and hydrocyanic acid, which interfere with the respiratory chain of living beings. One alternative treatment for this residue is the implementation of anaerobic reactors, which may enable increase in commercial value through the production of biogas. To provide a high retention of biomass in the system and increase the contact area of the microorganisms with the effluent, inert support means are used, which allow the application of higher loads and reduce the hydraulic detention time. Thus, this study aims to evaluate the performance of anaerobic treatment of starch wastewater, using two reactors with different support means, bamboo and PVC rings. The experiment was conducted in the Laboratory of Environmental Sanitation of the Western Paraná State University Campus Cascavel, using wastewater from the starch in the city of Toledo (PR). Two reactors used PVC with a diameter of 15 cm and 90 cm of length, resulting in a 1:6 ratio. As a conduit, 52 bamboo support rings were used, with an average of 10 cm in length, in one reactor and 325 rings of conduit with 4 cm of average length, resulting in a working volume of 6.00 and 7.98 L, respectively. All thirteen applied loads were gradually increased from 1.675 to 15.158 gL-1.d-1, until reaching the maximum load bearable by the reactors. When the system was stabilized, for each condition of applied load, the collecting of data was carried out for a period of fifteen days, through daily sampling at the entrance and at the exit of the reactors. The samples were analyzed for parameters: COD, total solids, pH, alkalinity, volatile acidity and biogas production. To determine the parameters COD and total, fixed and volatile soils, the methods described in the 2540B and 5220D Standard Methods for the Examination of Water and Wastewater (1998) were used; volatile acids and alkalinity was assessed according to the methodology proposed by Silva (1997). Five sampling points were installed along the length of the reactors to evaluate the process of digestion in the reactor. At these points, samples were collected in duplicate at the end of the period of data collection for each condition of applied load, as well as being analyzed according to parameters such as COD, acetic acid, propionic, and butyric acid, which were determined by high performance liquid chromatography, according to the methodology proposed by Leong & Shui (2002). Some instability in the system was observed in load 12 (12.394 gL-1.d-1), with values of AV / AT above 0.5 and a reduction in pH, but the system started showing signs of stability in the next load. The COD removal did not differ between the two reactors, reaching values of 99.72%. The reactor filled with bamboo had a higher biogas production, with a total production of up to 1.57 LL-1.d-1 and the reactor filled with PVC presented higher removal of total solids: 87.40%. Through the identification of volatile fatty acids from the samples collected along the the reactor, only acetic and propionic acid were found.